التوافق النفسي والاجتماعي ودوره في تحسين الأداء المرتبط بالمنافسة عند لاعبي الكرة الطائرة - بن التومي بلال (sports creativity, 2025)
This research examines the role of psychological and social adjustment in improving competitive performance among volleyball players. Given the lack of understanding of the psychological and social aspects of players and their impact on performance, we decided to delve into this topic. Our aim is to identify the role of psychological traits and social relationships in enhancing competitive performance among volleyball players. In this study, we employed a descriptive methodology with a sample of 40 players active in the top division of volleyball. The sample was selected randomly, and a questionnaire was used as the data collection tool. The most significant finding was that psychological and social adjustment plays a crucial role in improving competitive performance among volleyball players. One of the key recommendations is that coaches should focus on the psychological and social aspects of their players to foster positive relationships both within and outside the team, ultimately leading to higher performance levels.